Variability in asthma quality and costs in children with different Medicaid insurance plans in Maricopa County. (1st February 2019) - Rank, Matthew; Landman, Natalie; Harootunian, Gevork; Winscott, Michelle; Jain, Neil; Frey, Keith; Wilson, Gena; Drewek, Rupali; Parra-Roide, Lilia; Wilson, Charlton; Smoldt, Robert; Cortese, Denis
ABSTRACT: Objective : To describe the variation in asthma quality and costs among children with different Medicaid insurance plans. Methods : We used 2013 data from the Center for Health Information and Research, which houses a database that includes individuals who have Medicaid insurance in Arizona. We analyzed children ages 2–17 years-old who lived in Maricopa County, Arizona. Asthma medication ratio (AMR, a measure of appropriate asthma medication use), outpatient follow-up within 2 weeks after asthma-related hospitalization (a measure of continuity of care), asthma-related hospitalizations, and all emergency department (ED) visits were the primary quality metrics. Direct costs were reported in 2013 $US dollars. We used one-way analysis of variance to compare the health plans for AMR and per member cost (total, ER, and hospital), and the chi-squared test for the outpatient follow-up measure. We used coefficient of variation to identify variation of each measure across all individuals in the study. Results : In 2013, 90, 652 children in Maricopa County were identified as having asthma. The average patient-weighted AMR for children with persistent asthma was 0.35, well short of the goal of ≥0.70, and only 36% of hospitalized asthma patients had outpatient follow-up within 2 weeks of hospitalization. AMR, total costs, and ED costs varied significantly ( p <.0001) when comparing health plans while hospital costs and outpatient follow-up showed no significant variation. Conclusions : Targeting appropriate medication use for asthma may help reduce variation, improve outcomes, and increase healthcare value for children with asthma and Medicaid insurance in the US.